Measurement Acceptance of UWKS Academic Smart Mobile Applications Using UTAUT (Unified Theory of Acceptance and Use of Technology) - Rachmadi, Dio Gadang; Sunarto, Dewiyani; Mastan, Ignatius Adrian (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
UWKS Academic Smart Mobile is a smartphone application owned by the University of Wijaya Kusuma (UWK) Surabaya. In addition to provide facilities for students, Academic UWKS Smart Mobile also can be a competitive advantage. It makes the application developers want to know the level of acceptance UWKS Academic Smart Mobile on student UWK Surabaya. The solution of these problems were take measurements of the application uwks academic smart mobile uses the method utaut ( the unified theory of acceptance and use of technology )Tools for collecting data using questionnaires with 161 samples to do research. Sampling was conducted using Stratified Random Sampling (SRS) on the student UWK Surabaya. Descriptive analysis and analysis of validity and reliability using the software SPSS 16. For data analysis, Structural Equation Model (SEM) using AMOS 22 software.The results showed that the Performance Expectancy, Effort Expectancy and Social Influence positively affects Behavioral Intention UWKS Academic Smart Mobile. Facilitating Conditions and Behavioral Intention positively affects Use Behavior UWKS Academic Smart Mobile.